Comparative Study of PGPR Isolated from Crop Plants Mustard and Maize and Wild Medicinal Plant Lantana and their Potency for Enhancement of Wheat Plant - Rajesh Kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Comparative Study of PGPR Isolated from Crop Plants Mustard and Maize and Wild Medicinal Plant Lantana and their Potency for Enhancement of Wheat Plant